2017
DOI: 10.21037/jtd.2017.03.124
|View full text |Cite
|
Sign up to set email alerts
|

Pleural abrasion should not routinely preferred in treatment of primary spontaneous pneumothorax

Abstract: Background: The aim of this study was to find out whether thoracoscopic bullectomy with pleural abrasion (BLPA) could lower the recurrence ratio in primary spontaneous pneumothorax (PSP) patients compared with bullectomy alone. (4,700.69±1,591.56 vs. 4,211.45±1,207.7, P<0.01) were observed in BLPA group. There was no significant recurrence difference between BLPA group and bullectomy group (2.6% vs. 5.3%, P=0.30).Conclusions: Compared with bullectomy, BLPA could provide similar recurrence for PSP patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…A randomized trial by Lee et al established the efficacy of staple line coverage and concluded that pleural abrasion procedures may be replaced by visceral pleura coverage (18). Several reports have suggested the benefit of procedures without pleural abrasion, but this is still a controversial subject (19,20). Pleural abrasion results in more chest pain, pleuritis, loculated effusion, or hemothorax.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial by Lee et al established the efficacy of staple line coverage and concluded that pleural abrasion procedures may be replaced by visceral pleura coverage (18). Several reports have suggested the benefit of procedures without pleural abrasion, but this is still a controversial subject (19,20). Pleural abrasion results in more chest pain, pleuritis, loculated effusion, or hemothorax.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Nevertheless, the efficiency of pleural abrasion for pneumothorax patients has been questioned in recent years. [ 13 ] Pleurectomy versus pleural abrasion can reduce pneumothorax recurrence rates. [ 14 ] However, many surgeons refuse to use this technique just as the higher rate of post-operative complications, including bleedings and haematothorax with a need of reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Lung resection for etiology without pleurodesis and pleurectomy is an effective method in the treatment of PSP. [13] Long-term follow-up of these patients should be made concerning detecting recurrence and pneumothorax that may develop on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%